2021
DOI: 10.3390/cancers13050965
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-Infiltrating Lymphocytes (TILs) and PD-L1 Expression Correlate with Lymph Node Metastasis, High-Grade Transformation and Shorter Metastasis-Free Survival in Patients with Acinic Cell Carcinoma (AciCC) of the Salivary Glands

Abstract: Objectives: The aim of this study was to assess the number of tumour-infiltrating lymphocytes (TILs) and the expression of Programmed Cell Death 1 Ligand 1 (PD-L1) in Acinic Cell Carcinoma (AciCC) of the salivary glands, to enable a correlation with clinico-pathological features and to analyse their prognostic impact. Methods: This single centre retrospective study represents a cohort of 36 primary AciCCs with long-term clinical follow-up. Immunohistochemically defined immune cell subtypes, i.e., those express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Considering the role of TIL, intratumoral and marginal CD8+, intratumoral FOXP3+, and marginal CD3+ showed to be predictive of LNM. Hiss et al found significant evidence of the increased occurrence of LNM in high-grade acinic cell carcinomas, which also have a greater CD3+ expression with respect to low-grade tumors ( 30 ). In line with our findings, Kesar et al described that tumors with a high total CD8+ showed aggressive behavior in terms of nodal involvement ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of TIL, intratumoral and marginal CD8+, intratumoral FOXP3+, and marginal CD3+ showed to be predictive of LNM. Hiss et al found significant evidence of the increased occurrence of LNM in high-grade acinic cell carcinomas, which also have a greater CD3+ expression with respect to low-grade tumors ( 30 ). In line with our findings, Kesar et al described that tumors with a high total CD8+ showed aggressive behavior in terms of nodal involvement ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PD-L1 CPS was associated with a poor prognosis regarding metastasis-free survival. The authors concluded that increased immune cell infiltration of T and B cells as well as higher levels of PD-L1 expression in AcCC in association with high-grade transformation, lymph node metastasis, and an unfavorable prognosis suggests a relevant interaction between tumor cells and immune cell infiltrates in a subset of AcCCs, and might represent a rationale for immune checkpoint inhibition [94]. Finally, a study analyzing all histological subtypes including MECs and adenocarcinomas described significantly elevated CD3+, tumor proportion scores (TPS), combined positive scores (CPS), and immune cell scores (IC) in adenocarcinoma NOS compared to ACCs, MECs and AcCCs.…”
Section: Vinca Alkaloids/platinummentioning
confidence: 99%
“…Recent studies suggest that the spatial context of tumor infiltrating lymphocytes is an important prognostic determinant of tumor progression and response 1 , 2 , 3 . The distribution pattern of tumor infiltrating lymphocytes in the tumor microenvironment (TME) can be classified as three T cell infiltration phenotypes: immune-inflamed, immune-excluded and immune-desert, based on the spatial localization of immune cells with respect to the tumor and stromal compartments 4 .…”
Section: Introductionmentioning
confidence: 99%